(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Proton pump inhibitors (PPI) are drugs that suppress gastric acid secretion. Its use, without support from scientific evidence, can contribute to polypharmacy, lead to drug interactions and, in the long term, cause serious adverse reactions. Studies advise physicians to deprescribe PPI. A quick review of scientific evidence, also called a rapid systematic review, on the deprescribing of PPI was performed. Evidence searches were performed in the LILACS, Embase, PubMed and NICE evidence databases with the terms “omeprazole”, “proton pump inhibitors”, “deprescription”, “deprescribing”. At LILACS these descriptors were also used in Portuguese and Spanish. Of 118 studies identified, four systematic reviews were selected for analysis. Abrupt deprescribing was associated with an increased risk of symptom recurrence. Fear of symptom recurrence is one of the major barriers to patient-related deprescribing. Educational interventions directed at prescribers, pharmacists, and patients are effective strategies in the deprescribing of PPI. Deprescribing process showed to be feasible in different contexts, with different strategies. The process is most effective through actions with educational and guidance materials directed to health professionals and patients, and with the involvement or leadership of the pharmacist.